Synthesis of Fatty Alcohols from Oil Palm Using a Catalyst of Ni-Cu Supported onto Zeolite - L. Giraldo; G. Camargo; J. Tirano; J. C. Moreno-Piraján (E-Journal of Chemistry)
A series of Ni-Cu supported onto zeolite type ZSM-5 has been synthesized by direct hydrothermal method without template agent and characterized using XRD, FT-IR, NRM mass, SEM, CG and N2 adsorption techniques. The catalytic performance of the obtained materials was evaluated and utilized for the hydrogenation of palm oil at 453 K and 40 atmospheres of pressure. The results show that the samples exhibited typical hexagonal arrangement of mesoporous structure with high surface area and the heteroatoms were probably incorporated into the framework of ZSM-5. Catalytic tests show that the bimetallic incorporated materials were effective as catalysts in the hydrogenation of oil palm producing fatty alcohols typical.